Agritourism-capitalization possibility of rural community resources - Ciolac, Ramona; Adamov, Tabita; Popescu, Gabriela; Marin, Diana; Bodnár, Károly (Acta Carolus Robertus, 2022)
Agritourism activity supports rural development because it capitalize agricultural resources from rural area and community and it also use crafts, traditions and other resources of local community, thus ensuring long-term sustainable development. Agritourism can come as a salvation for the sustainable development of localities with specific resources, but also as a salvation in terms of passing on to future generations valuable resources, largely lost in many rural areas. In the maintenance of the tourist vocation of these localities, the inhabitants of these areas and the tourists must participate equally, the desired goal being the increase of tourists’ interest in these areas, the maintenance of the specific lifestyle and why not the profitability of the conservation of these resources for those involved. Where it is possible to ensure the conservation and valorization of these resources through tourism, villages have "a new chance at life", turning into permanent tourist locations. The sustainability of agritourism, or the "health" of the rural environment, derives from the fact that this activity cannot be dissociated from the economic, social and cultural life of the community. Between tourism and the environment there is a close relationship based on: environmental elements considered tourist attractions; tourist facilities and infrastructure; and the impacts generated by tourism development. The link between agritourism and the sustainability of rural communities derives from the definition of this activity.